The Effect of Air Alert Training on the Jump Shot Ability of Basketball Players from the Bintang Muda Padang Pariaman Team: PENGARUH LATIHAN AIR ALERT TERHADAP KEMAMPUAN JUMP SHOOT PEMAIN BOLA BASKET TEAM BINTANG MUDA PADANG PARIAMAN - Yunita, Pepi; Masrun; Yenes, Ronni; Syarli Lesmana, Heru (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the suboptimal jump shoot ability of basketball players from the Bintang Muda Padang Pariaman team. Air Alert training was used to improve lower limb explosive power, which plays an important role in performing a jump shoot. The purpose of this study was to determine the effect of Air Alerttraining on jump shoot ability. The research method used was an experimental design with a One Group Pretest-Posttest Design. The sample consisted of 15 players selected using a total sampling technique. The research instrument used was the Basketball Jump Shooting Accuracy Test (BJSAT). Data analysis was conducted using the Shapiro–Wilk test and paired sample t-test at a significance level of 0.05. The results showed an increase in the average score from 10.3 (pretest) to 14.5 (posttest) with a gain score of 4.2. The tvalue was 14.38 with a significance of 0.000 (p < 0.05), indicating a significant effect. It can be concluded that Air Alert training is effective in improving jump shoot ability.